Kongregacje dekanalne na tle zadań i obowiązków dziekanów w ustawodawstwie synodalnym diecezji włocławskiej w okresie potrydenckim - Gręźlikowski, Janusz (Prawo Kanoniczne, 2002)
Synod legislators from Wloclawek, while determining in detail the rights and duties of the deans, wanted them to guarantee increase of discipline, morality and Ethics amongst the priesthood as well as to contribute to revival of priesthood and were the tool of introduction into parish life the common, provincial and diocesan law. First of all, the following synods: bishop’s Stanislaw Kamkowski (1568) and bishops’s Hieronim Rozrażewski (1585,1586,1589 and 1598) as well as synods of bishop’s: Pawel Wolucki’s (1617, 1620 and 1622), Andrzej Lipski; s (1628) and Maciej Lubienski’s (1634) had decisive influence on from of dean’s office in Wloclawek diocese, its functioning and tasks. Amongst the tasks and duties of the deans, decanal congregations had very important role and greatness. They were considered as important tool of forming church discipline amongst the priesthood by oil Wloclawek’s synods post-trident period undertaking this subject. Synod legislators, referring to regulations of Trident Council, to Pastoral of cardinal Maciejowski and to resolutions of provincial synods, had obliged the deans to regular conventions of decanate priesthood as assemblies two times a year and they determined in detail the course, role and tasks of these decanal assemblies. By paying big attention to them in synod’s resolutions, they realized, how significant they role can be in revival of priesthood and increase of priesthood church discipline. Analyze of Wloclawek synod legislation allows to native in it certain continuity, when we are talking abut the contents of statutes dispositions. Bishop Stanislaw Kamkowski, a big protagonist of introduction of Trident reform into Wloclawek Church life, on his first synod in 1568 had initiated decanal congregations as meetings that gather priesthood, on which the dean was entitled to examine the decanate priesthood from education and existence and he had a duty to devolve necessary knowledge from theology and law. Merit of bishop Hieronim Rozrażewski was reactivation of decanal structures, revival and increase of the range of dean’s office as well as detailed determination of tasks and duties of deans, including those which are referring to congregations. On the base of legal norms of these two bishops, the following bishops: Pawel Wolucki and Andrzej Lipski had built legal regulations referring to dean’s office, structures and decanal congregations and also they had made more detailed. Bishop Maciej Lubieński, on synod in 1634, took care of decanal congregations to the highest extent. His directives included in synod’s resolutions can be called instruction for these meetings, however those directives were never called that way. In should be admitted that Trident reform within the range of revival and stimulation of decanal structures, amongst the others, thanks to reinforcement of dean’s office, determination of its duties and tasks and thanks to decanal congregations, found the appropriate understanding in synod legislation in Włocławek. It should be also supposed that in the second half of XVII century and later, after cessation of synod activity in Wloclawek diocese, dean’s office has been still developing and it played important role in priesthood and decanal congregations along with it.